Pengembangan Teknologi Produksi Khamir rhodotorula sp. Sebagai Agensia Pengendali Hayati Penyakit Antraknosa pada Cabai - Dian Indratmi (Jurnal Gamma, 2012)
Pengembangan Teknologi Produksi Khamir rhodotorula sp. Sebagai Agensia Pengendali Hayati Penyakit Antraknosa pada CabaiDian IndratmiStaf Pengajar Jurusan Agronomi, Fakultas Pertanian dan PeternakanUniversitas Muhammadiyah Malang e-mail: indratmi_dian@yahoo.co.idABSTRACTThe aimed of this research to find out a low cost media culture formulation for yeast fructoplant Rhodotorula sp. biomass production for their application on field to suppressed anthracnose disease on pepper.The laboratory experiment with Complete Randomized Design and 3 replication. There were 10 treatment, it’s M1 (rain tree pod extract + potato extract); M2 (rain tree pod extract + chilli extract ); M3 (corn meal+ chilli extract); M4 (sugar potato extract); M5 (sugar chilli extract); M6 (potato dextrose broth); M7 (corn solid media); M8 (100% chilli extract); M9 (sugar corn meal); dan M10 (100% rain tree pod extract) Results of the experiment indicated from 10 of the yeast media culture test 100%Chilli extract medium and rain tree pod extract + potato extract medium resulted better spore weight and cell density of Rhodotorula sp. yeast. Its shown with spore weight 0.4833 g/ 10 ml to 100% chilli extract and cell density 59.67 x 103 cell/ ml. At rain tree pod extract + potato extract medium, spore weight 0.4845 g / 10 ml with cell density 70.67x103 cell/ml. Production Rhodotorula sp. yeasy cell on solid medium can used corn medium.Key word : Colletrotichum gloeosporioides, Rhodotorula sp. , Biocontrol